HYDROGENOTUNGSTATO COMPLEXES WITH TIN HALOGENURES (IV): INFRARED AND MÖSSBAUER STUDIES - DINORA DE BARROS; MOUHAMADOU SEMBENE BOYE; LIBASSE DIOP (Journal of Engineering Studies and Research)
Six new hydrogenotungstato adducts and complexes have been synthesized and studied by infrared and Mössbauer techniques. The structures are mainly discrete, the anion behaving as a bidentate -one case- or a monodentate ligand in most cases. When extra hydrogen bonds are considered, supramolecular architectures may be obtained.